Synthesis of complex γ-lactones mediated by manganese(III) - Logan, A (2012)
This thesis details the development of manganese(III) acetate-mediated oxidative radical cyclisation methodology. In particular, the use of radicals to form complex, highly sterically congested and strained carbo- and heterocycles in a stereocontrolled manner is described. Chapter 1 gives a summary of the literature regarding three key areas relevant to this work. Radical reaction mechanisms are introduced, including the use of transition metals and lanthanides in C-centred radical cyclisations. The formation of highly sterically congested vicinal all-carbon quaternary stereocentres is also discussed. Finally, the use of radical cyclisation methodology for the synthesis of complex cyclic structures and applications in natural product total synthesis is examined. Chapter 2 gives an account of the manganese(III) acetate-mediated cyclisation of 5-pentenyl malonates bearing a terminal aryl group. The effects of the aryl group are tested with a range of electronically varied substituents. The formation of bi- and tricyclic cyclopentane-lactones bearing adjacent quaternary-quaternary-tertiary stereocentres is demonstrated. Chapter 3 demonstrates the synthesis of highly strained tricyclic bis-lactones. The metal complexes manganese(III) acetate and cerium(IV) ammonium nitrate are shown to give complementary stereoselectivity across a range of cyclisation substrates. Possible synthetic applications of tricyclic bis-lactones are also investigated. Chapter 4 details an asymmetric formal synthesis of the proteasome inhibitor salinosporamide A. An oxidative radical cyclisation forms the key heterocycle in Danishefsky’s synthesis of this biologically important molecule, and showcases the use of the radical chemistry in natural product synthesis. Full experimental details, selected NMR spectra, and X-ray crystallographic data are also provided.